Autophagy is induced under Zn limitation and contributes to Zn-limited stress tolerance in Arabidopsis (Arabidopsis thaliana). Issue 4 (4th July 2017) - Eguchi, Masatake; Kimura, Kazuhiko; Makino, Amane; Ishida, Hiroyuki
ABSTRACT: Autophagy is a degradation system for cellular components conserved in eukaryotes. In Arabidopsis, it is known that autophagy is crucial for growth under dark-induced carbon starvation and N deficiency. However, little is known about the relationship between autophagy and other nutrients. Here, we focused on the relationship between autophagy and Zn nutrition. We found that autophagy-deficient ( atg ) mutants showed an early senescence phenotype under Zn limitation and limited growth recovery from Zn limitation. Furthermore, we confirmed the induction of autophagy under Zn limitation by expression analysis of autophagy-related genes ( ATG s) and imaging analysis of autophagic bodies with green fluorescent protein-ATG8a (GFP-ATG8a). In atg mutants, although the Zn concentrations were similar to those of the wild-type plants, the transcript levels of Zn deficiency-inducible genes fluctuated more, and O2 – and H2 O2 levels increased more than in wild-type plants. These results suggest that autophagy is involved in intracellular Zn usage and suppresses the accumulation of reactive oxygen species (ROS) generated by Zn limitation.